2018
DOI: 10.1159/000485375
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Faecal Calprotectin Levels are a Reliable Non-Invasive Screening Tool for Small Bowel Crohn’s Disease in Patients Undergoing Capsule Endoscopy

Abstract: Background: Approximately 10% of Crohn’s disease (CD) patients have this disease affecting the small bowel (SB) beyond the reach of Ileo-colonoscopy. Capsule endoscopy (SBCE) is the recommended investigation for SB disease. An accurate and inexpensive biomarker would help identify at-risk patients. Aim: To examine the efficacy of faecal calprotectin (FC) and C-reactive protein (CRP) as predictors of SBCE findings in suspected and known CD. Methods: A prospective observational study. Consecutive patients referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…16 The predictive value of FC is well established in patients with colonic involvement of Crohn's disease, 17 and the addition of small bowel capsule endoscopy has been confirmed in several studies using inflammatory indices such as a Lewis score. 16,[18][19][20][21][22][23][24][25] Recent prospective studies have suggested that FC can be used as a screening tool before patients undergo capsule endoscopy; [26][27][28][29][30] however, these studies have been limited by sample size and statistical power. Therefore, we conducted an updated meta-analysis to provide pooled diagnostic accuracy and a cutoff value of FC for the diagnosis of small bowel Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%
“…16 The predictive value of FC is well established in patients with colonic involvement of Crohn's disease, 17 and the addition of small bowel capsule endoscopy has been confirmed in several studies using inflammatory indices such as a Lewis score. 16,[18][19][20][21][22][23][24][25] Recent prospective studies have suggested that FC can be used as a screening tool before patients undergo capsule endoscopy; [26][27][28][29][30] however, these studies have been limited by sample size and statistical power. Therefore, we conducted an updated meta-analysis to provide pooled diagnostic accuracy and a cutoff value of FC for the diagnosis of small bowel Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%
“…All the reported values of the sensitivity and specificity, according to different FC levels, are summarized in Table …”
Section: Resultsmentioning
confidence: 99%
“…All the reported values of the sensitivity and specificity, according to different FC levels, are summarized in Table 3. 22,[24][25][26][27][28][29][30][31][32][33][34] The small number of patients (four studies enrolled less than 30 patients and only three more than 100), as well as the retrospective design of five studies, 22,25,31,32,35 might limit the reliability of data (Table S1). Moreover, a direct comparison is not possible owing to the different criteria used to establish the diagnosis of CD, different scores, and cutoff values.…”
Section: Resultsmentioning
confidence: 99%
“…Upper GI endoscopy was nondiagnostic as well. While capsule endoscopy comes in handy to diagnose such cases and can be utilized, it is not available widely even in many tertiary care hospitals [10-11]. This case helps remind us of the variable clinical presentation of CD and highlights the fact that despite the commonality of this disease, it still can be a diagnostic challenge.…”
Section: Discussionmentioning
confidence: 99%